Daily Review of Antimicrobial Use Facilitates the Early Optimization of Antimicrobial Therapy and Improves Clinical Outcomes of Patients with Bloodstream Infections - Itoh, Yoshinori; Ohta, Hirotoshi; Goto, Takayuki; Yasuda, Koji; Niwa, Takashi; Shinoda, Yasutaka; Tsuchiya, Mayumi; Nakayama, Asami; Watanabe, Tamayo; Suzuki, Keiko; Murakami, Nobuo (Biological & pharmaceutical bulletin, 2016)
Insufficient information is available to confirm the beneficial effects of implementing an antimicrobial stewardship program in reducing mortality of patients with bloodstream infections. A single institutional cohort study was conducted to evaluate clinical outcomes after implementation of a daily review of antimicrobials used to treat patients with bloodstream infections. Subjects were allocated to groups receiving either intervention or nonintervention. After implementation of an antimicrobial stewardship program, the day from the onset of infection required to administer effective intravenous antimicrobial treatment was significantly shortened (p=0.022), and the rate of de-escalation was significantly elevated (p<0.001) compared with the nonintervention group. Further, the rate of 30-d death associated with bloodstream infection was siginificantly reduced from 11.4 to 5.4% (p=0.030) compared with the nonintervention group. The incidence of adverse events was significantly lower in the intervention group than in the nonintervention group (7.7 vs. 28.0%, p<0.001). Our present findings suggest that daily review of the use of antimicrobials was highly effective for optimizing early antimicrobial therapy and improved clinical outcomes of patients with bloodstream infections.